Division wise Loan Disbursement and Profitability of Bank: Evidence from Bangladesh - Antora, Lima Akter; Paul, Sujan Chandra; Or-Rosid, Md Harun (ETIKONOMI, 2025)
Research Originality: Loan disbursing in economically and industrially developed divisions of Bangladesh have profound impact on a bank’s profitability remaining other factors in considerations.Research Objectives: This study aims to investigate the effect of divisional loan disbursement on profitability and financial health of the banking sector in Bangladesh.Research Methods: The analysis is based on panel data from 44 banks, totaling 520 observations over an eighteen-year period from 2005 - 2022. To conduct this study, different models like Ordinary Least Square (OLS), Pooled Ordinary Least Square (POLS), Second Stage Least Square (2SLS), Generalized Method of Moments (GMM) are utilized.Empirical Results: The study found that there is favorable association between profit after tax and total revenue in all the model employed in the study. As opposed, PAT has an unfavorable association with Rangpur division’s loan disbursement and a total asset in all the model used in the study. In addition, the connections between PAT and loan disbursed in other is mixed but insignificant in nature.Implications: The empirical implications of this study are – lending economically and industrially developed or underdeveloped divisions of Bangladesh has too delicate relationship with a bank’s profit after tax.JEL Classification: E32, E43, G21How to Cite:Antora, L. A., Paul, S. C., & Rosid, M. H. (2025). Division wise Loan Disbursement and Profitability of Bank: Evidence from Bangladesh. Etikonomi, 24(1), 17 – 30. https://doi.org/10.15408/etk.v24i1.38326.